Prodrug and targeted delivery : towards better adme properties - Rautio, Jarkko (Methods and principles in medicinal chemistry, 2011)
This topical reference and handbook addresses the chemistry, pharmacology, toxicology and the patentability of prodrugs, perfectly mirroring the integrated approach prevalent in today's drug design